2007
DOI: 10.1016/j.genhosppsych.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Access to HAART and utilization of inpatient medical hospital services among HIV-infected patients with co-occurring serious mental illness and injection drug use

Abstract: Objective-Among HIV infected individuals we examined whether having a co-occurring serious mental illness (SMI) and injection drug use (IDU) impacts: (1) receipt of HAART and (2) utilization of inpatient HIV services, compared to those who have SMI only, IDU only, or neither.Methods-Demographic, clinical, and resource utilization data were collected from medical records of 5,119 patients in HIV primary care at 4 U.S. HIV care sites in different geographic regions with on-site mental health services in 2001. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…This finding builds on earlier cross-sectional evidence that suggests that those with SMI are as likely to initiate or access HAART compared with those without SMI [17,18,27]. It is also consistent with evidence that providers are willing to consider prescribing HAART to individuals with schizophrenia who are receiving psychiatric care [28].…”
Section: Discussionsupporting
confidence: 83%
“…This finding builds on earlier cross-sectional evidence that suggests that those with SMI are as likely to initiate or access HAART compared with those without SMI [17,18,27]. It is also consistent with evidence that providers are willing to consider prescribing HAART to individuals with schizophrenia who are receiving psychiatric care [28].…”
Section: Discussionsupporting
confidence: 83%
“…[9][10][11][12][13][14][15][16] It has been suggested that the cycle of crack cocaine use followed by drug-seeking activities makes it difficult to adhere to antiretroviral medication regimens or instructions given by an HIV primary care provider. 7,17 We also found that having unstable housing and having an annual income of less than $5000 were related to never having seen an HIV primary care provider and not currently receiving HAART. Homelessness and poverty have been shown to be common barriers to utilization of HIV care.…”
Section: 4mentioning
confidence: 70%
“…[4][5][6][7][8][9][10][11] With the introduction of highly active antiretroviral therapy (HAART) in 1996, overall rates of hospitalization among HIV-infected patients declined significantly, particularly for AIDS-related issues, 9 though subsequently admissions for other causes (liver disease, non-opportunistic infections) increased 1,2,4 and demonstrated ongoing health disparities for women, 1 patients with serious mental illness, 10 injection drug users 7,10 and African Americans. 1,5,8,11 In the HAART era, national HIV hospitalization costs were 3.2 billion in 2005, 12 and costs for readmissions in this population may be up to 32% higher than the index admission.…”
mentioning
confidence: 99%